APLIKASI GAME EDUKASI BELAJAR MENGHAFAL AYAT-AYAT PENDEK BERBASIS ANDROID MENGGUNAKAN METODE INTERPOLATION SEARCH (STUDI KASUS : TK SULAMUL ULUM) - Hardianto, Roki; Ajeng Listianingrum; Eva Tri Ningsih (Department of Information System Muhammadiyah University of Riau, 2024)
This research produces output in the form of android-based educational games that can be used in early childhood learning. The results of testing on students illustrate that games can motivate students in learning, especially the introduction of short verses. The interpolation search method helps users search for short verses to be learned.